Comparação do bloqueio do nervo femoral isolado e do bloqueio dos nervos femoral e ciático com a anestesia espinhal para controle da dor pós-operatória na artroplastia total de joelho: estudo prospectivo, duplamente encoberto e aleatório - Luiz Fernando Machado Soares (2017)
Total knee arthroplasty (TKA) is one of the most performed orthopedic surgeries currently, tending to increase progressively in the coming years. Postoperative pain may prolong hospitalization, negatively influence rehabilitation and challenge analgesia protocols for this procedure. There is controversy in the literature regarding the best anesthetic technique for TKA. This study compares the postoperative efficacy of isolated femoral nerve block and its association with sciatic nerve block in the analgesia of patients submitted to this surgery. Sixty patients were selected according to inclusion and exclusion criteria from a total of 72 patients selected for TKA. Of these, 43 were women and 17 were men. The mean age was 71.9 years (+ - 7.8 years). After randomization, they were divided into three groups: A, B and C. Group A (control) received spinal block (12-15 mg of 0.5% isobaric bupivacaine) and saline solution at the sites of femoral and sciatic nerve block. Group B received, in addition to spinal block, femoral nerve block (125 mg of ropivacaine 0.5% and 75 mcg clonidine) guided by ultrasound and nerve stimulation. Was made injection of saline solution into the sciatic nerve block site. In group C, the spinal, femoral and sciatic blocks were performed as described above. Pain was assessed using the visual analogue scale (VAS), with a gradual scale from 0 to 10 (0-2 = light; 3-7 = moderate; 8-10 = intense) immediately after surgery, after six hours, 12 hours, 24 hours and 48 Hours postoperatively. Both patient and evaluator did not know the substance used in peripheral (double blind) blockages and therefore which group they belonged to. We observed a decrease in postoperative pain in groups B and C compared to group A (control) after six hours and 12 hours after surgery (p <0.05). We concluded that both peripheral nerve blocks decreased postoperative pain in TKA, and the blocking of the femoral nerve associated with the sciatic nerve was more effective.